REFLEKSIVITAS PELAKU INDUSTRI KECIL PEMPEK PADA MASA PANDEMI DI KECAMATAN SEBERANG ULU SATU KOTA PALEMBANG - Rahmawati, eva; Diana Dewi Sartika; Waspodo, Waspodo (Media Bina Ilmiah, 2023)
This research examines small pempek industry players who are increasingly reflexive in anticipating risks during a pandemic, to be precise in the location of Seberang Ulu Satu District, Palembang City. The method used is descriptive qualitative using a case study strategy. There were seven informants in this study, consisting of key, main and supporting informants. Based on the results of this study, it can be shown that the pandemic has caused social anxiety and brought risks of economic loss to small pempek industry players. Various risk threats such as reduced buyers, decreased income, reduced workforce, increased raw material prices and marketing delays. This risk vulnerability phase requires the awareness of small pempek industry players to be more reflexive, to make changes in adaptive behavior to anticipate risk threats, namely through diversification. Diversification is an action or behavior effort to minimize risks due to a pandemic. This reflexivity is carried out based on the capabilities and experience of each industry player, so that pandemic events or situations that are out of control, which can disrupt the economy of small pempek industry players can be anticipated by reducing the amount of production, selling prices adjusted to the market, looking for materials cheaper raw materials, looking for additional income, online promotion, and even closing a business. All of these changes in behavior are a form of reflexivity for small pempek industry players to survive to be able to adapt and be individually responsible for anticipating risk threats during a pandemic so that financial prosperity is achieved in meeting the needs of daily life